Poltesa Press sebagai Publishing Service - Suhendra, Suhendra; Astuti, Theresia Widji; Agam, Beryaldi; Sanubary, Iklas; Marselina, Maya; Santoso, Pande Putu Agus (PUSAT PENELITIAN DAN PENGABDIAN PADA MASYARAKAT (PPPM) POLITEKNIK NEGERI SAMBAS, 2025)
Sambas State Polytechnic as a Higher Education Institution that has been established since 2008 still does not have an official publishing institution. Efforts to overcome this problem are made by building internal publications that can effectively support academic and research goals. Through community service activities, activities were carried out that aimed to establish an institution-owned publishing named Poltesa Press. Activities carried out include the formation of the organizational structure and single account of Poltesa Press, making the Poltesa Press emblem and website, making books to be published, proposing book ISBNs, printing books and proposing Poltesa Press to become a member of IKAPI. Based on the Decree of the Director of Sambas State Polytechnic, the organizational structure and single account of Poltesa Press were determined. The chosen Poltesa Press symbol was determined based on the results of the Poltesa Press team meeting. The first book published by Poltesa Press was titled “The Surefire Trick of Fishing Shrimp in the River”. The ISBN proposal of the book was submitted to the National Library. Official recognition as a legitimate publisher is done by proposing Poltesa Press to become a member of IKAPI in the West Kalimantan branch board.